Geneva convention iii commentary : relative to the treatment of prisoners of war - the geneva conventions of 12 august 1949 - Preux, Frederic Siordet, Claude Pilloud, Jean-Pierre Schoenholzer, Rene-Jean Wilhelm, Oscar H. Uhler, Henri Coursier Jean de. ([S.l.] : International Committee of the Red Cross, 1994)
764 pages.